2022
DOI: 10.3390/foods11121783
|View full text |Cite
|
Sign up to set email alerts
|

Cow’s Milk Antigens Content in Human Milk: A Scoping Review

Abstract: The functionality of breast milk in terms of immunity is well-known. Despite this, a significant proportion of breastfed infants exhibit sensitization to different potentially allergenic proteins and clinical reactivity (including anaphylaxis) early in life and before the introduction of complementary feeding for the first time. The potential induction of early oral tolerance to overcome early allergic sensitization through exposure to allergens in breast milk also remains controversial and not yet well-establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 67 publications
(205 reference statements)
2
12
0
Order By: Relevance
“…This publication found the presence of β-lactoglobulin, a bovine milk protein, in human breastmilk at similar levels previously published by Høst and Halken (range 0.9 – 150 µg/L) [ 9 , 10 ]. Interestingly, they found that in some breastmilk samples, β-lactoglobulin was detected up to 7 – 10 days after stopping the consumption of cow’s milk [ 9 ]. This review found a significant correlation between high levels of β-lactogobulin in breast milk to clinical manifestations such as diarrhea, vomiting, colic, or eczema, which are all typical non-IgE mediated symptoms [ 11 , 12 ].…”
Section: Can Food Allergens Through Breastmilk Lead To Symptoms?supporting
confidence: 81%
See 4 more Smart Citations
“…This publication found the presence of β-lactoglobulin, a bovine milk protein, in human breastmilk at similar levels previously published by Høst and Halken (range 0.9 – 150 µg/L) [ 9 , 10 ]. Interestingly, they found that in some breastmilk samples, β-lactoglobulin was detected up to 7 – 10 days after stopping the consumption of cow’s milk [ 9 ]. This review found a significant correlation between high levels of β-lactogobulin in breast milk to clinical manifestations such as diarrhea, vomiting, colic, or eczema, which are all typical non-IgE mediated symptoms [ 11 , 12 ].…”
Section: Can Food Allergens Through Breastmilk Lead To Symptoms?supporting
confidence: 81%
“…At the heart of the debate of non-IgE mediated allergy in breastfed infants, is the question to whether maternally consumed food allergens can lead to symptoms. A recent scoping review found 27 studies assessing bovine milk protein in breastmilk that included data on the type of sampling method, the sampling time, the lactation stage, maternal allergy status, and, most importantly, the impact on the infant [ 9 ]. This publication found the presence of β-lactoglobulin, a bovine milk protein, in human breastmilk at similar levels previously published by Høst and Halken (range 0.9 – 150 µg/L) [ 9 , 10 ].…”
Section: Can Food Allergens Through Breastmilk Lead To Symptoms?mentioning
confidence: 99%
See 3 more Smart Citations